Strategies for enhancing melanoma detection in clinical practice and improving patient outcomes - Wójtowicz, Elżbieta; Kulbat, Aleksandra; Zalasińska, Joanna; Wysocki, Wojciech M. (Family Medicine & Primary Care Review, 2024)
Melanoma, with its rising incidence, is a significant contributor to skin cancer-related fatalities. Early diagnosis of the tumor remains crucial for improving patients’ prognosis. This article describes the rising occurrence of melanoma among individuals with fair skin, particularly those with high sun exposure and tanning habits. It emphasizes significant geographic and ethnic disparities in melanoma incidence worldwide. Factors influencing patients’ prognoses, such as tumor biology, patient stress and healthcare system-related aspects, are scrutinized. The article presents comprehensive guidelines for diagnosing melanoma in everyday clinical practice, highlighting the importance of thorough full-body skin examinations, dermoscopy for all lesions and excision of uncertain nodular lesions. Moreover, the integration of clinical context and artificial intelligence tools in dermatology for early disease identification is explored. The synergy of medical expertise and advancements in artificial intelligence holds great potential for revolutionizing melanoma care and enhancing skin health management.